Gender, social class, and entrepreneurship: focusing female university students in an emerging country - Lima, Edmilson; Nelson, Reed; Nassif, Vânia Maria Jorge (Revista de Administração da UFSM, 2017)
Research worldwide has identified a strong association between social class and a variety of dimensions related to entrepreneurship including entrepreneurial intention, frequency of firm foundings, growth, success and other factors. Similarly, researchers have identified an association between gender and a series of entrepreneurial behaviors and outcomes. There is however very little research considering possible interactions between social class, gender and entrepreneurship, especially outside of the US and continental Europe. Using elite versus subelite university affiliation as a proxy for social class, the present article looks at the interaction between social class and gender as it relates to several aspects of entrepreneurship in four samples summing up 14,807 responses from Brazilian undergraduates. While supporting much of the existing research on social class and entrepreneurship and gender and entrepreneurship, it identifies a number of unexpected interactions between gender, social class and correlates of entrepreneurial behaviors.